2014
DOI: 10.1038/srep07373
|View full text |Cite
|
Sign up to set email alerts
|

Llama immunization with full-length VAR2CSA generates cross-reactive and inhibitory single-domain antibodies against the DBL1X domain

Abstract: VAR2CSA stands today as the leading vaccine candidate aiming to protect future pregnant women living in malaria endemic areas against the severe clinical outcomes of pregnancy associated malaria (PAM). The rational design of an efficient VAR2CSA-based vaccine relies on a profound understanding of the molecular interactions associated with P. falciparum infected erythrocyte sequestration in the placenta. Following immunization of a llama with the full-length VAR2CSA recombinant protein, we have expressed and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Several studies analysing the immune response to VAR2CSA have demonstrated that DBL4ε-specific antibodies are able to label and inhibit the adhesion of P. falciparum infected erythrocytes in a strain-independent manner, showing that this domain is surface-exposed in the full-length VAR2CSA 29 35 36 37 . Nanobodies raised against the full-length VAR2CSA, but with specificity to DBL4ε domains, were also found to be surface-reactive although not inhibitory 38 39 . These data and the fact that DBL4ε does not participate in the minimal binding region of VAR2CSA 21 22 , suggest that inhibition could involve steric hindrance and/or abolition of the native higher-order domain organisation.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies analysing the immune response to VAR2CSA have demonstrated that DBL4ε-specific antibodies are able to label and inhibit the adhesion of P. falciparum infected erythrocytes in a strain-independent manner, showing that this domain is surface-exposed in the full-length VAR2CSA 29 35 36 37 . Nanobodies raised against the full-length VAR2CSA, but with specificity to DBL4ε domains, were also found to be surface-reactive although not inhibitory 38 39 . These data and the fact that DBL4ε does not participate in the minimal binding region of VAR2CSA 21 22 , suggest that inhibition could involve steric hindrance and/or abolition of the native higher-order domain organisation.…”
Section: Discussionmentioning
confidence: 97%
“…Since nanobodies have only three hypervariable regions (CDRs), compared to antibody formats derived from conventional IgGs, these binders preferably recognize and bind conformational epitopes e.g. formed by enzymatic pockets of regulatory domains [ 57 , 58 ]. Consequently, binding of nanobodies often interferes with the function of the targeted antigen [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ditlev et al . 70 attributed the binding of a panel of alpaca V H Hs to multiple domains of the malarial VAR2CSA protein to an inherent ability of V H Hs to recognize subdominant epitopes, although limited understanding of the human conventional antibody response against VAR2CSA as well as irreproducibility of these reactivity patterns by llama V H Hs 71 complicated this assessment.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%